2016
DOI: 10.3892/or.2016.4967
|View full text |Cite
|
Sign up to set email alerts
|

ACE2 overexpression inhibits acquired platinum resistance-induced tumor angiogenesis in NSCLC

Abstract: Angiotensin II (AngII) is a multifunctional bioactive peptide in the renin-angiotensin system (RAS). Angiotensin-converting enzyme 2 (ACE2) is a newly identified component of RAS. We previously reported that ACE2 overexpression may inhibit cell growth and vascular endothelial growth factor (VEGF) production in vitro and in vivo. In the present study, we investigated the effect of ACE2 on tumor-associated angiogen-esis after the development of acquired platinum resistance in non-small cell lung cancer (NSCLC). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 19 publications
2
30
0
Order By: Relevance
“…Conversely, the activation of the alternative RAS, through Ang-(1–7) infusion or AT2R activation, can also reduce tumor growth. Cheng et al (2016) found that ACE2 overexpression may potentially suppress angiogenesis in non-small cell lung cancer (NSCLC) after the development of acquired platinum resistance. Namazi et al (2014) suggested that the combination of either captopril or captopril+losartan with innate and acquired tamoxifen resistance led to the prevention and even reversion of innate and acquired tamoxifen resistant phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the activation of the alternative RAS, through Ang-(1–7) infusion or AT2R activation, can also reduce tumor growth. Cheng et al (2016) found that ACE2 overexpression may potentially suppress angiogenesis in non-small cell lung cancer (NSCLC) after the development of acquired platinum resistance. Namazi et al (2014) suggested that the combination of either captopril or captopril+losartan with innate and acquired tamoxifen resistance led to the prevention and even reversion of innate and acquired tamoxifen resistant phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…One potential explanation is that first‐line chemotherapy selects for tumors that are more susceptible to angiogenesis inhibitors. Consistent with this notion, there are preclinical data in several tumor types suggesting that platinum resistance enhances secretion of or dependence on angiogenic factors like VEGF . In addition, the chemotherapy backbone may modulate the effect of angiogenesis blockade, as ramucirumab has shown clinical benefit in combination with paclitaxel in EG cancer but not with platinum‐based regimens.…”
Section: Discussionmentioning
confidence: 84%
“…Indeed, serum VEGF levels were elevated in COVID-19 patients (Huang et al, 2020) possibly triggered by hypoxia and inflammatory changes and contributing to increased vascular permeability and pulmonary edema. Interestingly, increased ACE2 expression was shown to reduce VEGF production in vitro and in vivo (Cheng et al, 2016) ameliorating increased vascular permeability during lung injury (Yu et al, 2016) raising the question of whether SARS-CoV-2-induced endothelial ACE2 downregulation could underlie this observation. These findings highlight the importance of monitoring VEGF levels in patients with COVID-19 and also suggests a possibility of introducing treatment modalities to target VEGF responses.…”
Section: Ace2 and Cvd Symptoms In Covid-19 Patientsmentioning
confidence: 99%